Pengaruh efektifitas pengendalian internal dan kesesuaian kompensasi terhadap kecenderungan kecurangan akuntansi (Survey pada perusahaan BUMN cabang Pekanbaru) - Delfi, Tiara; Anugerah, Rita; A, Al-azhar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this research is to find out the effectiveness of internal control and compensation compatibility on accounting fraud tendency. Data for this study was obtained from samples of all staff off accounting and finance department whose working at BUMN company branch Pekanbaru. This research is using survey methods which using questioner instrument which is delivered directly to BUMN branch Pekanbaru. Total respondents which is used in this research are 120 respondents (80%). The analyzing method is Double Regression methods using SPSS (Statistical Product and Service Solution) version 17. Result of the study indicates that the effectiveness of internal control and compensation compability negative influence to accounting fraud tendency. The coefficient of determination in this research are 33.6%, both variable jointly influence dependent variable as much as 52.8%, while 47.2% is influenced by other unclear variable.Keywords: Accounting Fraud Tendency. Effectiveness of Internal Control, Compensation Compatibility